2021
DOI: 10.1007/s11916-021-00938-3
|View full text |Cite
|
Sign up to set email alerts
|

Disinfectants In Interventional Practices

Abstract: Purpose of Review This review aims to provide relevant, aggregate information about a variety of disinfectants and antiseptics, along with potential utility and limitations. While not exhaustive, this review’s goal is to add to the body of literature available on this topic and give interventional providers and practitioners an additional resource to consider when performing procedures. Recent Findings In the current SARS-CoV2 epidemiological environment, infection cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 78 publications
0
7
0
2
Order By: Relevance
“…Disinfectants are not innocent chemicals free from side effects, and respiratory and skin diseases due to disinfectants have been frequently reported over time. Although the effects on the nervous system have not been studied in detail, headache due to disinfectants has been reported in a handful of studies [24][25][26]. The lack of studies investigating the relationship between disinfectants and migraine in the literature is an important deficit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disinfectants are not innocent chemicals free from side effects, and respiratory and skin diseases due to disinfectants have been frequently reported over time. Although the effects on the nervous system have not been studied in detail, headache due to disinfectants has been reported in a handful of studies [24][25][26]. The lack of studies investigating the relationship between disinfectants and migraine in the literature is an important deficit.…”
Section: Discussionmentioning
confidence: 99%
“… [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] .…”
Section: Uncited Referencesunclassified
“…Bacterial cells were subjected to different concentrations of sodium hypochlorite (commercial bleach with a stock concentration of 5%) to induce the cells to enter a compromised state (Liu et al, 2009 ; Fernandes et al, 2014 ; Ye et al, 2020 ). Dead cells were prepared by incubation with 5% of bleach (Aranke et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Considering that there is no optimized detection and treatment against NTM isolates, appropriate strategies need to be taken to minimize and control their spread [ 83 ]. Therefore, sterilization and use of disinfectants play a crucial role in proper NTM control, especially in medical care units [ 84 ]. Nonetheless, different NTM species have presented strong resistance to different disinfectants and have typically drawn more attention in the studies related to disinfectant-resistant bacteria [ 85 ].…”
Section: Importance Of Disinfection Mechanisms Of Ntm Speciesmentioning
confidence: 99%
“…As a strong sterilization system with a low cost, chlorination is often used to obtain high-quality water and offers residual disinfection [ 82 , 83 ]. However, some bacteria, particularly several NTM isolates, can overwhelm chlorine disinfection [ 84 , 87 ]. Some studies reported the high viability of M. fortuitum and M. avium rather than Escherichia coli during chlorine disinfection [ 87 , 88 ].…”
Section: Importance Of Disinfection Mechanisms Of Ntm Speciesmentioning
confidence: 99%